PENENTUAN HARGA JUAL KOPI BUBUK ARABIKA FLORES BAJAWA DI KOPERASI SERBA USAHA FA MASA DESA BEIWALI KECAMATAN BAJAWA KABUPATEN NGADA - Putri, Yuliana Harisna; Kapa, Maximillian M.J.; Bano, Maria (Buletin Ilmiah Impas, 2023)
This research was carried out at the Fa Masa, Beiwali subdistrict, Bajawa district, Ngada Regency, in May-June 2023. The purpose of this study was to find out 1) Determination of the selling price of Arabica Flores Bajawa ground coffee at the Fa Masa and 2) The difference profit derived from each package size from the sale of Flores Bajawa Arabica Coffee Powder at the Fa Masa. The data collected is in the form of primary and secondary data. Primary data was obtained through interviews with informants, namely managers and employees who work at the Fa Masa and secondary data obtained from jurnal literature, and previous research. To answer the first objective, the Full Costing method, and objectived were used. Secondly, the qualitative descriptive analisis method was used The results of the research showed that Fa Masa multi-purpose cooperative determiners the selling price of ground coffee packaging sizes at a price namely for a 500 gram packaging for IDR 90.000, a 250 gram packaging for IDR 45.000 and 100 gram for IDR 20.000. the profits obtained and sales of coffee in 500 gram packages amounted to Rp. 1,838,555, while profits from sales of 250 gram and 100 gram packages amounted to Rp. 631,005, and Rp. 238,055.